Systematic Literature Review: Identifikasi Jenis Kesalahan Siswa Dalam Menyelesaikan Soal Integral Tak-tentu dan Strategi Scaffolding yang Efektif - Selawati, Selawati; Syamsuri, Syamsuri; Yuhana, Yuyu (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to identify the types of errors that students often make in solving indefinite integral problems and develop effective scaffolding strategies to help students overcome these difficulties. The method used is Systematic Literature Review (SLR), by collecting and analyzing 15 research articles from 2014-2024 that are relevant to this topic. The results showed that frequent errors include conceptual, procedural, and computational errors. Some students had difficulty in understanding the basic concept of integral, while others made mistakes in applying the integral rules and proper solving procedures. Scaffolding is proven to be an effective strategy to improve students' understanding and skills in solving indefinite integral problems. By providing gradual and structured support, scaffolding helps students build strong conceptual understanding and overcome different types of errors. This study suggests the use of appropriate scaffolding strategies in mathematics learning to minimize students' errors and improve their achievement in solving indefinite integral problems. This research makes a significant contribution in the development of a more effective and focused approach to mathematics learning.